Body mass index and lung cancer risk in never smokers - Kagohashi, Katsunori (Radiology and oncology (Ljubljana), 2006)
Background. A relationship between body mass index (BMI) and lung cancer risk in never smokers has not been reported precisely. To evaluate the risk of lungcancer associated with BMI in never smokers, we conducted a case-control study. Methods. The relationship between BMI and the risk of lung cancer in never smokers was investigated in a study of 204 lung cancer cases and 398 controls admitted between 1987 and 2005. Controls were selected from hospitalized age-matched never-smoking patients with non-malignant respiratorydisease. Results. When compared with BMI of the leanestgroup (BMI = 20.8 to = 22.9 to = 25.0; p = 0.327). Similarly, no association in women was found between BMI and lung cancer in these three BMI groups (the second group, p = 0.639; the third group, p = 0.667; the highest group, p = 0.978) when compared with that of the leanest BMI group. Conclusions. Our present study indicated that the association between leanness and the risk of lung cancer might be influenced by other factors such as smoking.
Keywords: Adenocarcinoma; Adenokarcinom; Body Mass Index; Dejavniki tveganja; epidemiologija; Epidemiology; indeks telesne mase; Lung Neoplasms; Pljučne novotvorbe; pljučni rak; Risk Factors; rizični faktorji; Telesna masa, indeks